Foster Parent Stress - Jones, Graham; Morrissette, Patrick J. (Canadian Journal of Counselling and Psychotherapy, 2007)
Counsellors in private practice, community agencies, or school systems frequently interact with foster children and foster parents. Without an understanding of the systemic repercussions associated with foster parent stress, counsellors may be at a clinical disadvantage. This paper discusses research findings pertaining to foster parent stress and the implications these findings have for counsellors and counsellor educators. Eleven significant themes were generated from the data and indicate that foster parents experience a wide range of stressful events affecting their personal well-being, their relationship with foster children, and the professionals with whom they interact.